Development and validation of a questionnaire about hidden curriculum in medical institutes: A pilot study - Rauf, Ayesha; Fatima, Fozia; Gilani, Rehama; Shabnam, Nadia (Frontiers in Medicine, 2023)
This study aimed to develop and validate a questionnaire that can assess hidden curriculum in medical institutes. We used the exploratory sequential mixed methods design. It is a continuation of the qualitative work of researchers that was about hidden curriculum and the second part of qualitative, developed a questionnaire by an expert panel. The quantitative part validated the questionnaire using both exploratory factor analysis (EFA). The sample size was 301 and the participants were aged between 18-25 years of both genders from medical institutes. First, we generated a 90-item questionnaire based on a thematic analysis of the qualitative part. The expert panel ensured the questionnaire’s content validity. The experts removed the overlapped items and items that did not represent the specific theme and developed a 39-item questionnaire. Next, we validated the questionnaire. EFA constituted six factors with 39 high loading items, which extracted 62% of the variance. It was found that the 33-item questionnaire (removed six items) was satisfied with good psychometric properties. The developed 33-item questionnaire was valid and reliable to assess the hidden curriculum in medical institutes and hence, accountability of faculty and students in curricula and extracurricular combined with equal opportunity as one factor; communication and relationship with stakeholders combined with evidence-based reforms and implementations as the second factor, and student-centeredness and empowerment are considered the third main factor of the hidden curriculum in medical institutes. All these three main constructs were collectively used to measure hidden curriculum in medical institutes.